PENGARUH INNOVATIVE WORK BEHAVIOR TERHADAP KNOWLEDGE SHARING INTENTION KARYAWAN PT. CITRA RATNA NIRMALA - Johannes Kristiaji Hendarto; Angela Caroline; Agus Gunawan; Yoke Pribadi Kornariu (Media Bina Ilmiah, 2025)
Healthcare is a knowledge-intensive industry, emphasizing the necessity for organizations to maximize the knowledge of their employees. This research aims to analyze the influence of Innovative Work Behavior (IWB) on Knowledge Sharing Intention (KSI) at PT. Citra Ratna Nirmala, a healthcare institution in Indonesia. Through linear regression analysis, a positive influence of IWB on KSI was found at PT. Citra Ratna Nirmala. IWB was able to explain 33% of the variation in KSI. The frequency distribution results showed that the levels of IWB and KSI among employees at PT. Citra Ratna Nirmala were in the good category. To enhance KSI, the company can provide regular training, foster a collaborative environment, and offer rewards to employees who actively engage in knowledge sharing.